Pengaruh Retaliasi, Budaya Organisasi, Dan Norma Subjektif Terhadap Whistleblowing Intention Pada Lembaga Perkreditan Desa Se-Kecamatan Mengwi - Ni Kadek Ayu Suastini; Ni Wayan Yuniasih; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2023)
This study aims for determine the effect of retaliation, organizational culture, and subjective norms on whistleblowing intentions in LPDs throughout the Mengwi District. The population in this study were all LPD employees in Mengwi District, totaling 306 people (Badung Regency LPLPD, 2022). The number of LPDs in Mengwi District is 38 LPDs with a total 75 Samples. Technique Data analysis using linear regression analysis. The results of the study show that Retaliation has a negative effect on whistleblowing intentions at LPDs throughout the Mengwi District. Organizational culture has a positive effect on whistleblowing intentions in LPDs throughout the Mengwi District. Subjective norms have a positive effect on whistleblowing intentions in LPDs throughout the Mengwi District.